Akuntabilitas Komisi Pemilihan Umum Pada Pemilu 2019 Di Kabupaten Majene - Asrul, Muhammad; Ansari, Muh Isa; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to find out, analyze and describe the Election Commission Accountability Elections in 2019 at Majene Regency. This study used 5 informants. Data collection techniques were observation, interviews and documentation. Data analysis used interactive analysis models and used 3 types of triangulation in data validation. The result of this study showed that the accountability of the general election had been held optimally. There were no significant obstacles in the Majene general election commission and the holding of the 2019 general election was based on procedures by the organizers namely the General Election Commission, anticipating, maintaining, electon documents, and paid attention to the direction, fast and responsive to realize a successful and peaceful election, and institutions that worked together to be successful in holding of the 2019 general election.